Performance Analysis of 160WP Solar Panels as an Energy Source for 125 Watt Irrigation Pumps - Prasetyo, Hendrawan; Rozak, Ojak Abdul; Sumarno, Edy; Susilo, Joko Tri (UIR PRESS, 2026)
Solar energy has great potential as a source of renewable energy in Indonesia, especially in areas experiencing prolonged dry seasons. Long dry seasons that result in crop failure are one of the causes of declining agricultural yields, so appropriate technological solutions are needed for difficult agricultural land irrigation systems during the dry season. The need for water supply is important, but this system requires an independent source of electrical energy. The application of Solar Power Plants (PLTS) as a power source for 125W irrigation pumps is an alternative solution. This research aims to create and test a 160Wp solar power plant system as an energy source. The system made consists of solar panels, solar charge controller (SCC), 12V 100Ah LiFePO4 battery and inverter. Tests are carried out to measure the intensity of sunlight, voltage, current, and calculate the output power of the system, as well as the efficiency of the solar panels. The test results showed that the system produced an average solar irradiation of 636,72W/m² of 13,88V voltage, 3,78A current. Meanwhile, the system output power is 51,50W so that an efficiency of 21,07% is obtained. Thus, the solar PV system made is able to charge batteries up to 13,16V, this renewable energy source is proven to be efficient as an energy source for a 125W irrigation pump.